Histometric comparative study of the Harderian gland between newly hatching and two month old turkey bird (Tikrit Journal of Veterinary Science, 2025)
Twenty healthy turkey bird of  both sexes at two ages (1week, 2months) were used in the current study. They were selected from local farm in Iraq.  The Harder  gland were consisted of one lobe located in the medioposterior part  and ventrally aspect of the orbit behind the eye ball and   surrounded by the ocular muscles.  It was oval shape , pink to red in color, with rough surface  , it was compound  tubuloacinar gland. Many  ducts were drained in to central collecting duct of the wide irregular lumen. Thin connective tissue capsule of mesothelium  covered the gland completely, this capsule were sent trabecula  which dividing the gland into a lot of  lobules. The gland lined with columnar cells epithelia different in heights, with basally located dark nucleus and light stained cytoplasm which contained secretary vacuoles. The secretary unites were incompletely surrounded by myoepithelial cells, the dark elongated Myoepithelial cells were clearly noticed.